Canva sebagai Media Peningkatan Kreativitas Mendesain Iklan Slogan dan Poster pada Model Project-Based Learning. - Fitri Zulhandayani (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Technological developments are the reason a teacher must participate in improving teaching abilities with innovative learning methods. The use of technological media in the teaching process will have many benefits and be able to increase student creativity, especially in advertising material, slogans and posters. Media that is easy for students to have been their gadgets, along with their social media. Various information that can improve students' abilities can be accessed easily on the internet. So that students are accustomed to applying many things using their gadgets and the internet. Canva is an application that is easy for students to access, and its use is also not complicated to learn. This study aims to provide an explanation that the Project-Based Learning model is capable of being an effort to improve students' ability to creatively compose advertising text, slogans, and posters. The method used in this research is the Classroom Action Research (CAR) method which is directly investigated by the teacher (researcher). This type of research is also used with a descriptive approach where the research results will be described in detail. Based on the research that has been done, the results obtained are that the Project-Based Learning model implemented by using the Canva application is able to increase student creativity in designing advertisements, slogans and posters very creatively